Position specific physical demands in different phases of competitive matches in national level women`s football - Mäkiniemi, J. K.; Savolainen, E. H.; Finni, T.; Ihalainen, J. K. (Biology of Sport, 2023)
The purpose of the present study was twofold: to investigate position-specific physical match demands of national level women`s football; and to examine if demands change during a match (comparison between first and second half and in 15-minute intervals). Seven teams from the Finnish National League participated in the study. Eighty-five players met the inclusion criteria, and a total of 340 individual match observations from 68 individual matches were included for analysis. The Polar Team Pro -player tracking system (with 10 Hz GPS units, including 200 Hz tri-axial accelerometer, gyroscope, magnetometer and HR monitor) was used to assess positional data and HR response of the players. This study demonstrated that women`s national level football matches place a range of physical demands on players, which in general were highest for wide midfielders, and lowest for central defenders. Wide midfielders and forwards performed significantly more `very high-speed` running, sprinting, accelerations, and decelerations than other outfield positions (p < 0.05). HRmean varied from 84-87% of HRmax and was significantly lower for central defenders than central midfielders (p < 0.001). External load variables varied during a match and generally decreased especially after 60 minutes of play compared to first 15-min period of the match. Present study showed that national level women football players` positional differences in match demands are similar to those reported with elite players in previous studies. On national level, players` physical performance tended to decrease towards the end of the match, especially in terms of total distance (~10%), high-speed running (~20%), and decelerations (~20%).